Growth Performance of One Year Old Seedlings of Ironwood (Eusideroxylon zwageri Teijsm. & Binn.) Varieties - Bambang Irawan (Institut Pertanian Bogor (IPB University), 2012)
Four Eusideroxylon zwageri Teijsm. & Binn. varieties had been described. A study on growth performance of one-year old seedlings of E. zwageri varieties had been conducted to study the comparison of shoot growth performance and survival among E. zwageri varieties. The varieties were exilis, grandis, ovoidus, and zwageri. The study was conducted in Jambi, Indonesia for one year using complete randomized design. Four E. zwageri varieties were used as factor with 6 replications. Each consists of 6 seedlings therefore, the total number of seedlings were 144. The results showed that survival and shoot growth performance of E. zwageri seedlings were significantly different among varieties. Stem height of E. zwageri seedlings was significantly different among some varieties. The results related to stem diameter showed different characteristics among E. zwageri seedlings, zwageri variety had the biggest diameter. It was significantly different from ovoidus and exilis, but not significantly different from grandis. The differences among E. zwageri seedlings in shoot dry weight parameter were identical to the parameter of stem diameter. The lowest value of branch angle belonged to zwageri. Based on Duncan multiple range test, it was significantly different from other varieties except grandis. Generally, zwageri shows the best growth performance among seedlings of E. zwageri varieties.